(untitled) (International Journal of Environmental Sciences, 2025)
The purposes of this research were: 1) to development of English interactive approach and collaborative learning instructional model based on Thai Culture context to enhance reading comprehension ability and happiness learning for undergraduate students 2) to evaluate the quality of the developed instructional model English interactive approach and collaborative learning instructional model based on Thai culture context. The research procedure was divided into 3 phases. The first phase was to develop a reading instructional model based on English Interactive Approach and Collaborative Learning Based On Thai Culture Context.The second phase was to construct the research instruments. The third phase was to evaluate the quality of the developed instructional model by implementing with 30 students at faculty of education ,Suratthani Rajabhat University.The samples were simple random sampling selected from the third year students. The research instruments were the reading comprehension test ,questionnaire, and learning log. The data were analyzed using t-test. The findings of this study were as follows: The English interactive approach and collaborative learning instructional model based on Thai Culture Context consisted of 4 components : 1) Concept 2. Objectives , 3) learning procedures are included activating world knowledge, predicting and questioning, read and summarizing , discussion and reflect, and making graphic organizer 4. Evaluation . An independent T- test was conducted to determine the sample group demonstrated different performance across reading comprehension ability. Result of the test revealed that the student’s English Reading comprehension ability significantly increased after the intervention at a statistical level of significant of .05 level